A safe place - Trottier, Maxine; Friedman, Judith, 1945- (Morton Grove, IL : A. Whitman, 1997)
To escape her father's abuse, Emily and her mother come to a shelter where they find a safe place to stay with other women and children in similar circumstances.
Keywords: Women's shelters -- Fiction; Family violence -- Fiction